2018
DOI: 10.18203/2349-2902.isj20182777
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of local anaesthesia in lateral internal anal sphincterotomy for chronic anal fissure

Abstract: Background: Fissure in Ano is one of the common and most painful anorectal conditions encountered in surgical practice. Inspite of several conservative treatment options, surgical treatment in the form of Lateral Anal Spincterotomy (LAS) remains the gold standard of treatment for Chronic Anal Fissures (CAF).Methods: Prospective comparative study conducted on 90 patients randomly divided into two groups Group A under Local anaesthesia (LA) and Group B under Spinal anaesthesia (SA) respectively. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Arora et al 18 also found local anaesthesia is effective as a day care surgery for fissures as good healing rates were obtained. Goudar et al 19 found no statistically difference in the pain at surgery, but anaesthesia appreciably reduced the pain postoperatively in LA group at 5th h and 24 h after surgery. Hospital stay in LA group is significantly less when compared to SA group (1.92, vs. 3.75 days, respectively).…”
Section: Discussionmentioning
confidence: 89%
“…Arora et al 18 also found local anaesthesia is effective as a day care surgery for fissures as good healing rates were obtained. Goudar et al 19 found no statistically difference in the pain at surgery, but anaesthesia appreciably reduced the pain postoperatively in LA group at 5th h and 24 h after surgery. Hospital stay in LA group is significantly less when compared to SA group (1.92, vs. 3.75 days, respectively).…”
Section: Discussionmentioning
confidence: 89%